Environmental assessment of development project : a guide for planners and managers - Nagarajan, V.; Okot-Uma, R. W'o (London : The Commonwealth Secretariat and SFI Publishing, 1999)
Environment Management
Keywords: Environmental development; Environmental assesment; Global aspect; Environmental impact